NOU 2014:10 - Proposal for New Rules Regarding Criminal Insanity and Related Issues, Norway post-22 July - Gröning, Linda; Rieber-Mohn, Georg Fredrik (Bergen Journal of Criminal Law & Criminal Justice, 2015)
The criminal case in the aftermath of the terrorist attack in the centre of Oslo and on Utøya on 22 July 2011 raised a wide-ranging discussion on the way Norwegian criminal law tackles offenders with mental disorders. The discussion conducted in the public debate concerned particularly the configuration of rules on criminal insanity, the role of experts in criminal justice and the need for particular sanctions for criminally insane offenders. The backdrop for this debate was to a large extent the fact that Norwegian criminal law uses a ‘medical model’ for the definition of criminal insanity. Under section 44 of the Criminal Code, a defendant that is psychotic at the time of the offence is absolved from criminal responsibility. This provision essentially ‘equates’ criminal insanity with psychosis, and does not operate with any criteria requiring causality, or any other additional (‘psychological’) criteria as is the case in many countries. It has been questioned - particularly after the 22 July case - whether the medical model gives an erroneous delimitation of who should be absolved from criminal responsibility. It has also been questioned whether the experts (most often psychiatrists) have too much power in the determination of whether a defendant is criminally insane. To investigate the need for legislative change regarding these issues, a committee was appointed by the government by way of royal resolution on 25 January 2013. The committee presented its recommendation on 28 october 2014 in the report NOU 2014:10: Criminal capacity, expert knowledge, and the protection of society (Skyldevne, sakkyndighet og samfunnsvern). This document presents the committee's main findings.